Positronium-hydrogen atom elastic scattering at medium energies - Adhikari, S. K.; Mandal, P. (Iop Publishing Ltd, 2000)
We study the elastic scattering of positronium atoms by hydrogen atoms at medium energies using partial-wave Born-Oppenheimer (BO) exchange amplitudes and report accurate BO cross sections in the energy range 0 to 60 eV. The present BO results agree with a 22-state R-matrix and a five-state coupled-channel model potential calculation, but disagree strongly with a conventional close-coupling calculation as well as its input BO amplitudes at medium energies.